PINK1 Alleviates Cognitive Impairments via Attenuating Pathological Tau Aggregation in a Mouse Model of Tauopathy - Jiang, Xing Jun; Wu, Yan Qing; Ma, Rong; Chang, Yan Min; Li, Lu Lu; Zhu, Jia Hui; Liu, Gong Ping; Li, Gang (Frontiers in Cell and Developmental Biology, 2022)
As a primary cause of dementia and death in older people, Alzheimer’s disease (AD) has become a common problem and challenge worldwide. Abnormal accumulation of tau proteins in the brain is a hallmark pathology of AD and is closely related to the clinical progression and severity of cognitive deficits. Here, we found that overexpression of phosphatase and tensin homolog (PTEN)-induced kinase 1 (PINK1) effectively promoted the degradation of tau, thereby rescuing neuron loss, synaptic damage, and cognitive impairments in a mouse model of tauopathy with AAV-full-length human Tau (hTau) injected into the hippocampal CA1 area (hTau mice). Overexpression of PINK1 activated autophagy, and chloroquine but not MG132 reversed the PINK1-induced decrease in human Tau levels and cognitive improvement in hTau mice. Furthermore, PINK1 also ameliorated mitochondrial dysfunction induced by hTau. Taken together, our data revealed that PINK1 overexpression promoted degradation of abnormal accumulated tau via the autophagy-lysosome pathway, indicating that PINK1 may be a potential target for AD treatment.